2014
DOI: 10.1039/c4cc01243g
|View full text |Cite
|
Sign up to set email alerts
|

A quasi-solid-state rechargeable lithium–oxygen battery based on a gel polymer electrolyte with an ionic liquid

Abstract: A quasi-solid-state lithium-oxygen battery constructed using a gel polymer electrolyte with an ionic liquid is proposed. The battery architecture incorporates a design feature that can be easily scaled up in size for use in large systems. The feasibility study demonstrates that the battery operates successfully for repeated discharge-charge cycles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
85
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 90 publications
(91 citation statements)
references
References 27 publications
4
85
0
2
Order By: Relevance
“…However, after the 50 th cycle, both CeO 2 and CeO 2 eAg electrodes are covered with blocky amorphous structure beneath thick and smooth layers because of the incomplete decomposition of discharge product and oxidation of the side reaction from the electrolyte decomposition ( Fig. 6(b) and (c), which is well consistent with the reported results [45,46]. These by-products were identified to be Li 2 CO 3 and Li 2 O 2 by the corresponding XRD patterns ( Fig.…”
Section: Resultssupporting
confidence: 93%
“…However, after the 50 th cycle, both CeO 2 and CeO 2 eAg electrodes are covered with blocky amorphous structure beneath thick and smooth layers because of the incomplete decomposition of discharge product and oxidation of the side reaction from the electrolyte decomposition ( Fig. 6(b) and (c), which is well consistent with the reported results [45,46]. These by-products were identified to be Li 2 CO 3 and Li 2 O 2 by the corresponding XRD patterns ( Fig.…”
Section: Resultssupporting
confidence: 93%
“…However, for the PGE battery, the R ct decreases as cycling progresses and the R ss increase only slightly. Lee [15] et al reported the degradation of the composite polymer separator due to the reaction of Li 2 O 2 with polymer. In this work, the superior stability of PGE battery may be the evidence that our polymer gel exhibits good tolerance to the attack of Li 2 O 2 .…”
Section: Resultsmentioning
confidence: 99%
“…Although replacing organic liquid electrolytes with nonflammable, high thermal stability and electrochemical stability ionic liquid is an alternative approach to enhance the safety of the battery [7], for the practical application of the Li-O 2 battery, the most important limitation is the critical operating environment. Much of the research on the Li-O 2 battery was conducted in closed purity or high-purity oxygen atmosphere [8,9]; unfortunately, the energy output was markedly deteriorated once the operating environment altered to ambient air, especially under low oxygen partial pressure [10][11][12][13]. Meanwhile, it should be noted that continuous supply of dry O 2 from ambient air is a problem, and closed Li-O 2 system (storing oxygen directly in the battery or in a tank) is much larger and heavier than an open system; this will significantly reduce the energy density of the practical Li-O 2 battery unless a low-weight and high-pressure tank is used [14].…”
Section: Introductionmentioning
confidence: 99%